Total arch replacement versus proximal aortic replacement in acute type A aortic dissection: Aggressive versus conservative. Issue 12 (10th September 2022) - Jubouri, Matti; Ansari, Daniyal Matin; Zaqout, Feras; Bashir, Mohamad; Idhrees, Mohammed
Abstract: Background: Acute type A aortic dissection (ATAAD) is a life‐threatening medical condition requiring urgent surgical attention. It is estimated that 50% of ATAAD die within 24 h of onset, with the mortality rate is increasing by 1%–2% every additional hour without prompt intervention. A variety of ATAAD surgical repair techniques exist which has sparked controversy within the literature, with the main two strategies being proximal aortic replacement (PAR) and total arch replacement (TAR). Nevertheless, the question of which of these two strategies if the more optimal is still debatable. Aims: This commentary aims to discuss the recent study by Sa and colleagues which presents a pooled analysis of Kaplan–Meier‐derived individual patient data from studies with follow‐up comparing aggressive (TAR) and conservative (PAR) approaches to manage ATAAD patients. Methods: A comprehensive literature search was performed using multiple electronic databases including PubMed, Ovid, Google Scholar, EMBASE, and Scopus to collate the relevant research evidence. Results: The more aggressive TAR approach for treating ATAAD seems to yield more favorable results including more optimal long‐term survival as well as a lower need for reoperation. The frozen elephant trunk (FET) technique can be considered the mainstay TAR technique. Conclusion: It is valid to conclude that TAR with FET is the superior strategy for managing ATAAD patients.